Influence of Eurasian snow depth anomaly on the Indian summer monsoon circulation (MAUSAM, 2003)
The Historical Soviet Daily Snow Depth (HSDSD) version II data set has been used to examine the empirical relationship between the winter/spring snow depth anomaly over three different regions of Eurasia and Indian Summer Monsoon Rainfall (ISMR). HSDSD data show that the difference in snow depth between two extreme years is most prominent over western Eurasia in the month of April and the inverse relationship between the spring snow depth anomaly and the following ISMR is very robust with correlation coefficient of –0.43 at 5% significant level. Examination of seasonal mean circulation pattern using NCEP/NCAR reanalysed data shows that low level atmospheric temperature difference between two extreme years of high and low western Eurasia snow depth in April can be as large as 10°C which gives rise to anomalous cyclonic circulation over the Caspian Sea and this may be responsible for affecting the monsoon circulation over India. Results also show that there is a complete phase reversal in the dipole structure of the upper tropospheric velocity potential anomaly from the deficient to excess ISMR irrespective of occurrence of different phases of ENSO events or high/low Eurasian snow. However, during opposite phases of ENSO, the divergence center has east-west shift as compared to the high Eurasian snow when the divergence center shifts to the southeast over Australia.